Pulsed laser diode based photoacoustic tomography system using multiple acoustic reflector based single element ultrasound transducers - Kalva, Sandeep Kumar (2019)
Conventional photoacoustic tomography (PAT) systems use bulky, expensive Q-switched Nd:YAG lasers which limits its usage in clinics. The low repetition rate of these lasers makes them not suitable for real-time imaging as well. Compact pulsed laser diodes (PLD) are being currently used for PAT systems due to their high repetition rates and compact in size. These lasers can be mounted inside the PAT circular scanning geometry making the PAT system more portable. Using acoustic reflector based single-element ultrasound transducer (SUTR), the scanning radius can be reduced thereby making the PAT system more compact. In this work, we present a portable, high frame rate, more compact second generation PLD-PAT system using eight SUTRs in circular scanning geometry. This system provides high frame rate of ~1 Hz. We demonstrate the performance of this system using phantom imaging studies.